Hubungan Tingkat Kecukupan Gizi, Tingkat Pengetahuan Ibu, dan Tinggi Badan Orangtua dengan Stunting pada Balita di Wilayah Kerja Puskesmas Tambak Wedi Surabaya - Rizqita Catur Wulandari; Lailatul Muniroh (Amerta Nutrition, 2020)
Background:Stunting is a failure to thrives in under five children condition that causes difficulty to achieves physical and cognitive development in optimal condition. Puskesmas Tambak Wedi as one of the health centers that have increased prevalence of stunting in toddlers by 2.7% from 2017 to 2018. It indicated that the prevention and management of stunting in Surabaya should be optimized so that the prevalence could be reduced. Objectives: The objective was to analyze the correlation between adequacy level of nutrients,mother's knowledge level,and height of parents with the incidence of stunting in Puskesmas Tambak Wedi.Methods: Observational study with a case-control design. The population was 1,143 toddlers. The sample size is 48 toddlers consisting of 24 stunting and non-stunting toddlers selected through simple random sampling. The dependent variable was stunting. The independent variable was the nutritional adequacy,mother’s knowledge level, and parent’s height. The data was analyzed by the chi-square test and simple logistic regression. Results: There were significant correlation between level of energy adequacy(p=0.02;OR=0.11), protein(p=0.018;OR=2.3), calcium(p=0.023;OR=0.2), and mother’s knowledge(p=0.029;OR=-0.265) with stunting in toddler. Father’s(P=0.77) and mother’s(P=0.76) height were not correlated with stunting in a toddler. Non-stunted children were more likely to have better adequacy levels of energy(58.3%), protein(100%), and calcium(58.3%) compared to stunted children. Toddlers who have a mother with good knowledge were have a lower risk of stunting by 0.265 times than toddlers whose mothers lack knowledge.Conclusions: Adequacy levels of nutrients and level of mother knowledge in non-stunting toddlers were better than stunting toddlers aged 24-59 months in Puskesmas Tambak Wedi SurabayaABSTRAKLatar Belakang: Stunting merupakan masalah pertumbuhan fisik yang disebabkan oleh kurangnya kecukupan gizi, rendahnya pengetahuan gizi, serta tinggi badan orangtua. Puskesmas Tambak Wedi Surabaya merupakan salah satu puskemas yang mengalami peningkatan prevalensi stunting 2,7% dari tahun 2017. Meningkatnya angka prevalensi menandakan bahwa pencegahan dan penanganan stunting di Surabaya harus dioptimalkan agar prevalensinya dapat ditekan.Tujuan: Menganalisis hubungan tingkat kecukupan zat gizi (energi, protein, kalsium), tingkat pengetahuan ibu dan tinggi badan orangtua dengan stunting di Puskesmas Tambak Wedi.Metode: Penelitian ini merupakan penelitian observasional dengan desain case control. Besar sampel adalah 48 balita yang  terdiri dari sampel kasus (24 balita stunting) dan sampel kontrol (24 balita non-stunting). Variabel dependen adalah stunting. Variabel independen adalah tingkat kecukupan energi, protein, kalsium, tingkat pengetahuan ibu, dan tinggi badan orangtua. Analisis data menggunakan uji statistik chi-square dan regresi sederhana.Hasil: Terdapat hubungan antara tingkat kecukupan energi (p=0,02;OR=0,11), protein (p=0,018;OR=2,3), kalsium (p=0,023;OR=0,2), pengetahuan ibu (p=0,029;OR=‒0,265) dengan kejadian stunting pada balita. Tinggi badan ayah (p=0,77) dan ibu (p=0,76) tidak memiliki hubungan dengan kejadian stunting pada balita di Puskesmas Tambak Wedi.Kesimpulan: Tingkat kecukupan zat gizi dan tingkat pengetahuan ibu pada balita non-stunting lebih baik daripada balita stunting. Tingkat kecukupan zat gizi meliputi energi, protein, kalsium dan pengetahuan ibu memiliki hubungan dengan stunting pada balita usia 24-59 bulan di wilayah kerja Puskesmas Tambak Wedi Surabaya.